De nuevo acerca de Elsa Morante y María Zambrano. Algunas consideraciones sobre el amor, la piedad y la historia - Martínez Garrido, Elisa (Cuadernos de Filología Italiana, 2010)
This essay deals with the important role of piety, love and history in the works of Elsa Morante and María Zambrano. Special emphasis is given to the importance of the «poetic reason» of María Zambrano in the creative work of the Italian writer, specially in La Storia (1974), in Aracoeli (1982) and in the essays collected in Pro e contro la bomba atomica (1987). The Andalusian thinker was probably the mentor and guide of the young Italian writer during her exile in Rome (1952-1964) and acted as a source of philosophical inspiration to the Italian author, due in part to the mediation of Araceli Zambrano, a closed friend of Elsa Morante.
Keywords: Elsa Morante; María Zambrano; The «poetic reason»; Piety; Love; History and the other